2021
DOI: 10.1002/adfm.202104630
|View full text |Cite
|
Sign up to set email alerts
|

A Checkpoint‐Regulatable Immune Niche Created by Injectable Hydrogel for Tumor Therapy

Abstract: Current programmed death‐1 ligand (PD‐L1)‐based therapy focuses on local tumors. However, circulating exosomal PD‐L1 possesses inherent anti‐PD‐L1 blockade resistance and dominates tumor metastasis, playing a critical role in systemic immunosuppression. Therefore, the efficacy of immune checkpoint therapy depends on simultaneously decreasing tumoral and circulating exosomal PD‐L1. However, such therapeutic platforms have never been reported so far. Herein, a PD‐L1 checkpoint‐regulatable immune niche created by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…In spite of the excellent antitumor effects, low water solubility, poor metabolic stability and bioavailability, short half-life and poor tumor targeting capability have been proven almost to be an insurmountable obstacle for clinical translations of Que (Dabeek & Marra, 2019 ). Recent progresses in nanotechnology offer more possibilities to overcome these drawbacks of drugs themselves, which can efficiently encapsulate them and ameliorate their pharmacokinetics and pharmacodynamic profiles (Zhou et al., 2020 ; Li et al., 2021a,b ; Zhang et al., 2022 ). Interestingly, nanoparticles are capable of passively accumulating into tumor sites as a result of incomplete vessels and lymphatic blockage termed as enhanced permeability and retention (EPR) effect (Fang et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the excellent antitumor effects, low water solubility, poor metabolic stability and bioavailability, short half-life and poor tumor targeting capability have been proven almost to be an insurmountable obstacle for clinical translations of Que (Dabeek & Marra, 2019 ). Recent progresses in nanotechnology offer more possibilities to overcome these drawbacks of drugs themselves, which can efficiently encapsulate them and ameliorate their pharmacokinetics and pharmacodynamic profiles (Zhou et al., 2020 ; Li et al., 2021a,b ; Zhang et al., 2022 ). Interestingly, nanoparticles are capable of passively accumulating into tumor sites as a result of incomplete vessels and lymphatic blockage termed as enhanced permeability and retention (EPR) effect (Fang et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…reported a cancer cell membrane-derived hydrogel scaffold loaded with Ca 2+ channel inhibitor dimethyl amiloride (DMA) and cyclin-dependent kinase 5 inhibitor roscovitine for cancer treatment. In this system, cancer cell membrane, DMA and roscovitine were chosen with the aim of creating an antigen depot, suppressing Ca 2+ -governed exosome secretion and down-regulating tumor cell PD-L1 expression, respectively ( 52 ).…”
Section: Injectable Hydrogels Targeting Immunosuppressive Tumor Microenvironmentmentioning
confidence: 99%
“…Li et al reported a cancer cell membrane-derived hydrogel scaffold loaded with Ca 2+ channel inhibitor dimethyl amiloride (DMA) and cyclin-dependent kinase 5 inhibitor roscovitine for cancer treatment. In this system, cancer cell membrane, DMA and roscovitine were chosen with the aim of creating an antigen depot, suppressing Ca 2+ -governed exosome secretion and downregulating tumor cell PD-L1 expression, respectively (52). CTLA-4 is expressed on activated Th1 cells and CTLs, and binds to co-stimulatory molecules CD80 and CD86 of antigenpresenting cells, thereby inhibiting the activation and proliferation of T cells (53).…”
Section: Injectable Hydrogels Targeting Immunosuppressive Tumor Micro...mentioning
confidence: 99%
“…Cytotoxic T-lymphocyte protein 4 (CTLA-4) and programmed cell death protein 1 (PD-1) are the most two characterized. These molecules are self-tolerant under normal physiological contexts but easily powerless by malignancy [ 38 , 39 ]. Cancer cells aim to bind them with self-expressed specific receptors so that antitumor signalling and immune attack will be prevented.…”
Section: Tumor Immunotherapy and 3d Scaffold Biomaterials: A Brief Su...mentioning
confidence: 99%